Salidroside impedes Ang II-infused myocardial fibrosis by activating the SIRT1-Nrf2 pathway - Xi Zhu; Zhen Hai; Zhongping Ning (Iranian Journal of Basic Medical Sciences)
Objective(s): This research examined the protective function of salidroside (SAL) against angiotensin II (Ang II)-infused myocardial fibrosis and its associated mechanism.Materials and Methods: The C57BL/6 male murine models (n=24) received either saline solution or Ang II (1500 ng/kg/day) subcutaneously and an oral dosage of SAL (50 mg/kg/day) once daily for 28 days. Newborn Sprague-Dawley (SD) rats were used to isolate atrial fibroblasts.Results: The fibrotic region was raised by Ang II infusion, while SAL treatment inhibited it. Collagen I and III expression was raised by Ang II induction, but SAL therapy reduced their expression. SAL therapy also decreased the expression of other fibroblast differentiation-related markers induced by Ang II infusion. It elevated SIRT1, Nrf2, and HO-1 levels in atrial fibroblasts. Additionally, SAL significantly inhibited atrial fibroblasts, whereas EX527, an inhibitor of SIRT1, noticeably increased the migration ability. Furthermore, SAL suppressed intracellular ROS production and oxidative stress in Ang II-infused atrial fibroblasts. Conclusion: SAL protects against myocardial fibrosis infused by Ang II by activating the SIRT1-Nrf2 pathway.